Perfect Will Theology: Divine Agency in Reformed Scholasticism As against Sua´rez, Episcopius, Descartes, and Spinoza - Bac, J. Martin (Brill's Series in Church History and Religious Culture Ser., 2010)
This book revisits the four major early-modern debates concerning the will of God. It appears that Reformed scholasticism advocated a particular and consistent relationship between divine knowledge, will, and power, which was altered by Jesuits, Remonstrants, Descartes, and Spinoza.